Lord, How I Want to Be in That Number! On the Blessing of UNESCO World Heritage Listing - Enrico Bertacchini; Federico Revelli; Roberto Zotti (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies the impact of UNESCO World Heritage List (WHL) inscription on income and property values in the Italian municipalities that had their sites inscribed during the past two decades. To address the selection bias and identify the causal impact of inscription, we focus on sites included in the national 'tentative list' (i.e., list of candidates for subsequent nomination) and exploit the plausibly exogenous timing of inscription conditional upon entering the list. The evidence from an event study analysis suggests that WHL listing has a significant impact on the level and distribution of income. Possible underlying mechanisms are discussed.
Keywords: H24; H71; H73; 330; UNESCO World Heritage List; economic impact; real estate market; tourism